2019
DOI: 10.1080/09500340.2019.1589006
|View full text |Cite
|
Sign up to set email alerts
|

Graininess characterization by multidimensional scaling

Abstract: A validation of the graininess attribute was made by means of a psychophysical experiment and the multidimensional scaling algorithm. A visual experiment was designed to obtain graininess differences to be used like the dissimilarity matrix in the MDS algorithm. The results revealed that two dimensions are needed to characterize the graininess effect. The BYK-mac-i instrument and a gonio-hyperspectral imaging system were employed to evaluate the statistical dimensions. On one hand, the first dimension correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The variability associated with the individual observer response was 30%, and the inter-observer variability was 35%. These variability values are high compared to other visual experiments performed with the same procedure and the same objective [17,18]. This result is indicative of the difficulty observers have in perceiving different samples in terms of graininess as reflected by the randomness of their responses.…”
Section: Resultsmentioning
confidence: 64%
“…The variability associated with the individual observer response was 30%, and the inter-observer variability was 35%. These variability values are high compared to other visual experiments performed with the same procedure and the same objective [17,18]. This result is indicative of the difficulty observers have in perceiving different samples in terms of graininess as reflected by the randomness of their responses.…”
Section: Resultsmentioning
confidence: 64%
“…However, few works about establishing a graininess scale have been published. One previous work applied multidimensional scaling [16] and conducted a specific visual experiment. The results showed that two dimensions were necessary to characterize the graininess effect.…”
Section: Introductionmentioning
confidence: 99%
“…The physical factors that contribute to graininess are the type, size, disorientation and agglomeration of gonioapparent particles [2,8,13]. While there is no consensus regarding the analysis of graininess, some authors have proposed the use of radiometry and the combination of various parameters such as pigment concentration, scattering, absorption and lightness for this purpose [13][14][15].…”
Section: Introductionmentioning
confidence: 99%